A systematic review and meta-analysis on the efficacy of postoperative radiotherapy after gross total resection of intracranial solitary fibrous tumors - Min Kyun Na; Kyu-Sun Choi; Tae Ho Lim; Hyungoo Shin; Juncheol Lee; Heekyung Lee; Wonhee Kim; Jae Guk Kim; Youngsuk Cho; Chiwon Ahn; Jae Hwan Kim; Bo-Hyoung Jang; et al. (Scientific Reports)
Abstract The efficacy of postoperative radiotherapy (PORT) after gross total resection (GTR) for intracranial solitary fibrous tumors (SFT) remains unclear due to the inconsistent results of previous studies, with some studies suggesting improved outcomes in progression-free survival (PFS) and overall survival (OS), while others report no significant benefit. Therefore, by evaluating and synthesizing data from relevant studies, we aimed to investigate the role of PORT, as compared with surgery alone, in survival outcomes after GTR of intracranial SFT. A systematic literature search, adhering to PRISMA guidelines and using Medline, Embase, and the Cochrane Library to identify relevant literature. The outcomes of interest included progression-free survival (PFS), overall survival (OS), and metastasis-free survival (MFS) at 3, 5, and 10 years, respectively. Differences between the two cohorts (GTR + PORT vs. GTR only) were estimated by calculating the hazard ratios. Twelve studies, including data from 419 patients (GTR + PORT, n = 225 vs. GTR, n = 194), were selected for meta-analysis. Pooled hazard ratios revealed that the PORT cohort showed sustained superiority in both PFS and OS compared with the surgery-only cohort after GTR of the tumor. These results were consistent with those of a subgroup analysis that focused on grade 2 and 3 intracranial SFT. However, no significant improvement was observed in MFS with PORT addition. This study underscores the importance of PORT in enhancing the PFS and OS of patients with intracranial SFT after GTR. These findings suggest that PORT should be considered an effective treatment strategy for all patients with intracranial SFT, irrespective of the extent of resection.